2017
DOI: 10.1128/aac.01636-16
|View full text |Cite
|
Sign up to set email alerts
|

Active-Site Protonation States in an Acyl-Enzyme Intermediate of a Class A β-Lactamase with a Monobactam Substrate

Abstract: The monobactam antibiotic aztreonam is used to treat cystic fibrosis patients with chronic pulmonary infections colonized by Pseudomonas aeruginosa strains expressing CTX-M extended-spectrum β-lactamases. The protonation states of active-site residues that are responsible for hydrolysis have been determined previously for the apo form of a CTX-M β-lactamase but not for a monobactam acyl-enzyme intermediate. Here we used neutron and high-resolution X-ray crystallography to probe the mechanism by which CTX-M ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…As the pH 6.3 structure is identical to the pH 7.9 complex, this indicates the pK a of Lys73 is likely between pH 5.3 and 6.3, significantly lower than the estimate of 8.0 to 8.5 in previous studies of β-lactam hydrolysis (41). Additionally, computational predictions indicated similar disparity in Lys73 pK a between the acyl-enzyme complexes of avibactam and β-lactam inhibitor cefoxitin (6.24 versus 7.82; SI Appendix, Table S2) (11,42). Although these calculations were performed without using thermodynamic integration based on extensive explicit-solvent molecular dynamics simulations as done by others and were thus less accurate (41), they suggested that it would be of interest to further probe Lys73 pK a .…”
Section: Resultsmentioning
confidence: 66%
“…As the pH 6.3 structure is identical to the pH 7.9 complex, this indicates the pK a of Lys73 is likely between pH 5.3 and 6.3, significantly lower than the estimate of 8.0 to 8.5 in previous studies of β-lactam hydrolysis (41). Additionally, computational predictions indicated similar disparity in Lys73 pK a between the acyl-enzyme complexes of avibactam and β-lactam inhibitor cefoxitin (6.24 versus 7.82; SI Appendix, Table S2) (11,42). Although these calculations were performed without using thermodynamic integration based on extensive explicit-solvent molecular dynamics simulations as done by others and were thus less accurate (41), they suggested that it would be of interest to further probe Lys73 pK a .…”
Section: Resultsmentioning
confidence: 66%
“…Overall, our structures reveal that Ser70 is primed by deprotonation for nucleophilic attack on the AVI C-7 atom. It is still uncertain if this deprotonation is driven by Lys73 or Glu166 via a catalytic water that bridges both Glu166 and Ser70 (17)(18)(19)(20)(21)(22). Using both highresolution structural studies and molecular dynamics simulations, both Lys73 and Ser130 are also believed to participate in a proton shuttle resulting in the protonation of the AVI N-6 in the acylation step (15,23).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the study by Nichols et al (28) observed a proton transfer from Ser-70 to Glu-166 in the active site of class A ␤-lactamase CTX-M upon binding of a non-electrophilic ligand, lending experimental support to this model. Very recently, Vandavasi et al (29) reported for the first time structures of CTX-M in the acyl-enzyme complex with a monobactam, with Lys-73 indeed deprotonated to serve as general base for the acylation reaction. All these results support the model that the protonated Lys-73 in the apo-state can become deprotonated upon substrate binding to initiate the acylation reaction.…”
Section: Discussionmentioning
confidence: 99%